Minimum wages in Kenya - Mabel Andalón; Carmen Pagés (Institute for the Study of Labor (IZA), 2008)
This paper examines the performance of minimum wage legislation in Kenya, both in terms of its coverage and enforcement as well as in terms of their implications for wages and employment. Our findings based on the 1998/99 labor force data - the last labor force survey available - indicate that minimum wages, which, in principle, apply to all salaried employees, were better enforced and had stronger effects in the non-agricultural industry than in the agricultural one. More specifically, our results suggest that (i) compliance rates were higher in occupations other than agriculture, (ii) minimum wages were positively associated with wages of low-educated workers and women in non-agricultural activities, while no such relationship is found for workers in agriculture, and (iii) higher minimum wages were associated with a lower share of workers in formal activities in a given occupation and location. Our estimates indicate that a 10 percent point increase in the minimum to median wage ratio could be associated with a decline in the share of formal employment of between 1.2-5.6 percentage points and an increase of between 2.7-5.9 points in the share of self-employment.
Keywords: J23; 330; Minimum wages; employment; wage; Kenya; Mindestlohn; Wirkungsanalyse; Lohn; Beschäftigungseffekt; Branche; Informeller Sektor; Kenia